Boosting Listening Skills in Low English Proficiency Learners: A Study on Podcast-Based Audio Scripting Method - Efendi, Rahman; Nur, Rafi'ah; Ammade, Salasiah; Latifa, Ammang; Larekeng, Siti Hajar (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
Listening, the most commonly utilized language skill, is paramount in everyday communication and educational settings. Recognizing the significance of listening comprehension and the challenges associated with teaching it, researchers have explored innovative methods such as podcasts and audio scripting to enhance listening skills. This study examines the efficacy of employing podcasts through the audio scripting method in improving students' listening abilities. The research adopts a quasi-experimental design with an equivalent control group to investigate the impact of this method on listening learning. The experimental group received instruction through podcasts and audio scripting, while the control group followed traditional listening exercises. Pre-tests and post-tests were administered to both groups to measure listening proficiency. The findings indicate a positive correlation between the audio scripting method and enhanced listening skills, with the experimental group showing significant improvement compared to the control group. These results suggest that audio scripting is an effective pedagogical approach for enhancing listening comprehension. Consequently, incorporating audio scripting into the curriculum offers a promising avenue for bolstering students' listening proficiency, which is crucial for their academic success and professional development in healthcare. Further research is recommended to explore this method's long-term effects and potential applications across different educational contexts.